2005
DOI: 10.1024/0300-9831.75.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dementia and Nutrition-Related Factors and Disorders: An Overview

Abstract: This review gives a brief overview of the main types of dementia and summarizes current thinking on the relationship between nutritional-related factors and disorders, and dementia. Dementia is a multi-factor pathological condition, and nutrition is one factor that may play a role on its onset and progression. An optimal intake of nutrients doesn't protect people from dementia. However, studies in this area show that inadequate dietary habits, which are of particular concern in elderly populations, may increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 0 publications
1
17
0
5
Order By: Relevance
“…This possibility should not be surprising, given the accumulating evidence that the risk of developing AD can be influenced by many factors (Cupples et al, 2004) including newly discovered gene-gene interactions (Borroni et al, 2004;Bernardini et al, 2005;Dunckley et al, 2005;Lambert et al, 2005;Papassotiropoulos et al, 2005) and gene-race interactions (Green et al, 2002;Gureje et al, 2006), as well as interactions with other medical (Evans et al, 2004), and lifestyle/environmental factors (Mutter et al, 2004;Bird, 2005;Salerno-Kennedy and Cashman, 2005), all of which contribute to disease pathogenesis in poorly understood ways. More work is needed to understand the factors in family history that confer AD risk and their influence on brain structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility should not be surprising, given the accumulating evidence that the risk of developing AD can be influenced by many factors (Cupples et al, 2004) including newly discovered gene-gene interactions (Borroni et al, 2004;Bernardini et al, 2005;Dunckley et al, 2005;Lambert et al, 2005;Papassotiropoulos et al, 2005) and gene-race interactions (Green et al, 2002;Gureje et al, 2006), as well as interactions with other medical (Evans et al, 2004), and lifestyle/environmental factors (Mutter et al, 2004;Bird, 2005;Salerno-Kennedy and Cashman, 2005), all of which contribute to disease pathogenesis in poorly understood ways. More work is needed to understand the factors in family history that confer AD risk and their influence on brain structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…While a complete review of the effects of nutrition, diet, and physical activity on risk of dementia is beyond the scope of this paper, it is to be noted that both increased physical activity [63], and certain nutritional elements, such as unsaturated fats, vitamin C, E, B6, B12, and folate [64,65] are associated with a lower risk of dementia and AD. Conversely, diets high in saturated fat are found to increase risk of AD [66,67], and lead to impaired cognitive performance in animal models [68].…”
Section: Nutrition and Physical Activity As Mitigating Factorsmentioning
confidence: 97%
“…In fact, bioactive compounds, such as antioxidants, mostly contained in fruits and vegetables, are important for the protection against oxidative and nitrosative stress, and these micronutrients have been related with aging itself and the pathophysiology of some age-related illnesses, including cognitive impairment and dementia [182]. While a growing body of knowledge demonstrates both the importance of oxidative stress in the etiology of dementia and the efficacy of antioxidant treatment in animal and cellular models, studies in humans are presently inconclusive [183,184]. In fact, epidemiological studies have demonstrated that dietary intake of natural or synthetic products with a putative antioxidant effect, mainly vitamin E, improve cognitive function and reduce the risk of AD [185,186].…”
Section: High Intakes Of Cereals Fruits and Vegetables In Admentioning
confidence: 99%